Development and application of the CL&Pol polarisable force field for ionic liquid-based electrolytes - Wilson, Tayla Lee (Department of Chemistry, 2026)
Ionic liquids (ILs) are a fascinating class of molecular systems due to diverse and promising applications, including the potential use as electrolyte systems, replacing traditional volatile organic electrolytes. The appeal of ILs for such applications lies in the favourable properties, such as high diffusivity, thermal and electrochemical stability, and low volatility. Molecular dynamics (MD) simulation is a powerful tool for studying the physical properties of liquids; however, whereas traditional solvents are typically well described using classical, fixed-charge force fields (FFs), explicit inclusion of polarisation is essential for accurate description of IL dynamics. Consequently, the development and application of polarisable FFs for ILs is a necessary focus within IL research. The first aim of this work was therefore to extensively validate the recently developed Drude-based CL&Pol FF for six pure ILs and five alkali-earth containing IL-electrolytes. Reproducibility and precision are not often addressed when MD simulation is used to calculate thermophysical properties, yet without quantification of uncertainty, the value of a validation study is questionable. Hence, statistically meaningful uncertainties were reported for all properties as a 95 % confidence interval of the mean over replicate simulations. The simulation protocol was further validated by using well-known theoretical relationships (e.g., the Stokes Einstein and Nernst-Einstein equations) to confirm the internal consistency of key calculated transport properties. The accuracy of calculated properties of pure ILs varied, with average errors as low as 1 % for density to 35 % for viscosity, and 50 % for conductivity. Most properties could be calculated with uncertainties of ~20 %, while calculated conductivities had uncertainties of ~50 %. The second aim of this work involved the further development of the van der Waals component of the intermolecular interaction. The CL&Pol Lennard-Jones (LJ) parameters are carried over from its fixed-charge predecessor, CL&P. The parameters are then adjusted with prescribed scaling of the LJ well-depth (ε) to remove the induction contribution, making it transferable to the Drude FF featuring explicit polarisation. While scaling of ε produces reasonably accurate ii transport properties, the resulting induction-free LJ potentials for interactions involving the alkali metals do not reproduce the ab initio exchange-dispersion potentials, producing theoretically unsatisfactory van der Waals interactions. Furthermore, the existing OPLS ε parameters for the alkali metals do not correlate with the strength of the ab initio dispersion interactions, warranting reconsideration of these parameters. Thus, this work presents a stable and robust protocol for obtaining van der Waals potential parameters compatible with a Drude FF without the need of scaling, based on first-principles resolution of the dispersion and exchange components of the potential using Symmetry-Adapted Perturbation Theory (SAPT). However, while overall interaction energies can be accurately obtained with small basis sets, this is due to error cancellation in the components. Consequently, the f2+SAPT0 complete basis set (CBS) methodology was developed using the extended AHB21x5 dataset of anion-neutral dimers. This method uses basis set extrapolation and scaling of SAPT0 components to provide dispersion and exchange components with an average deviation of ~10 % from higher order SAPT2+/CBS equivalents. Finally, investigation into various potentials showed that Halgren's buffered LJ potential provides a description of the van der Waals interactions more consistent with the equivalent f2+SAPT0/CBS components, particularly at short range, than is offered by the CL&Pol scaled LJ potential.